Entomologische Chronik (James Edward Collin, F. R. E. S.). - Kenneth, G. V.; Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1970)
In memoriam James Edward Collin, F. R. E. S., *16.03.1876 +16.06.1968.